Isolasi dan Karakterisasi Senyawa Kimia dari Kulit Batang Manggis (Garcinia mangostana Linn) Isolation and Characterization of Chemical Compound from Bark of Mangosteen (Garcinia mangostana Linn) - Lia Destiarti; Ari Widiyantoro; Elvi Rusmiyanto; Maryati Maryati; Harlia Harlia; Ratu Safitri; Unang Supratman (Masyarakat Peneliti Kayu Indonesia, 2009)
The purpose of this research is to isolate and characterize chemical compound from bark of mangosteen. Bark of mangosteen was macerated with methanol. The extract from that process was fractionated with n-hexane, methylen chloride, and ethyl acetate. Ethyl acetate fraction was separated and purified by vacuum column chromatography, gravitation column chromatography, and preparative thin layer chromatography. The relative pure compound was afforded from ethyl acetate fraction of mangosteen bark (8.5 mg) resulting from 1.5 kg of mangosteen bark. The yellow amorphous powder of compound melts at 114 116ºC (uncorrected). The purity of compounds was tested by 1 and 2 dimension thin layer chromatography which gave one spot on TLC plate. The ultraviolet-visible (in CH3OH solvent) spectrum showed absorption maximum at 318 nm (sinamoyl group/band I), 258 (shoulder), and 243 nm (benzoyl group/band II). Addition of NaOH caused batochromic shift of band I and band II predicted as two hydroxyl at C-4’ and C-7, respectively. The infrared spectrum displayed absorption bands of OH stretching at 3436 cm-1, C-H stretching at 2920 cm-1, C=O stretching at 1631 cm-1, C-O-C stretching at 1094 cm-1, and C-H aromatics bending at 970-800 cm-1. A molecular ion in the FABMS at m/z 271.36 [M+H] + was consistent for the molecular formula C15H10O5. The 1H NMR spectrum showed characteristic resonances of a flavone. Based on the result of phytochemical test and analysis of the spectrum, it is predicted that the compound belongs to flavone, a kind of flavonoids which has hydroxyl at C-5, C-7, and C-4.